2013
DOI: 10.3899/jrheum.121521
|View full text |Cite
|
Sign up to set email alerts
|

Flares in Rheumatoid Arthritis: Frequency and Management. A Report from the BRASS Registry

Abstract: Patients with RA experienced flares more often when noted to be in higher disease activity states than when in remission and reported changes in disease-modifying antirheumatic drugs or biologics more frequently when flares were of longer duration. There is a need to prospectively study symptom intensity and duration of flare in relation to disease activity and consider self-management strategies in the development of a measure of flare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 19 publications
(35 reference statements)
0
50
2
Order By: Relevance
“…We utilized data from the Brigham and Women's Hospital Rheumatoid Arthritis Sequential Study (BRASS; Clinical-Trials.gov identifier NCT01793103), which was initiated in 2003-2004. Details concerning the study design have been reported elsewhere ( [30][31][32]; for further details, see http:// www.brassstudy.org.). The BRASS Registry is a single-center, prospective, observational longitudinal cohort of .1,200 adults with established or recent-onset RA who are being followed by a hospital-based practice of 21 rheumatologists in Boston.…”
Section: Methodsmentioning
confidence: 99%
“…We utilized data from the Brigham and Women's Hospital Rheumatoid Arthritis Sequential Study (BRASS; Clinical-Trials.gov identifier NCT01793103), which was initiated in 2003-2004. Details concerning the study design have been reported elsewhere ( [30][31][32]; for further details, see http:// www.brassstudy.org.). The BRASS Registry is a single-center, prospective, observational longitudinal cohort of .1,200 adults with established or recent-onset RA who are being followed by a hospital-based practice of 21 rheumatologists in Boston.…”
Section: Methodsmentioning
confidence: 99%
“…The term “flare” is often used to describe episodes of disease worsening in RA, which are often unexplained and debilitating 4 . Flares can vary widely in frequency, duration, and intensity 5 , and until recently, there has been little consensus on how to identify or define RA flares. For example, patients may use the word “flare” to describe any increase (transient or sustained) in RA symptoms such as joint pain, stiffness, or fatigue 6 .…”
Section: Flare In Rheumatoid Arthritismentioning
confidence: 99%
“…Furthermore, studies have demonstrated that improvements in these disease‐specific outcomes are associated with reduced pain and improved physical function, health‐related quality of life, and work productivity , suggesting that minimizing the amount of time RA patients spend with MHDAS is beneficial. Even brief periods of MHDAS (<3 months) are associated with progression of joint damage and worsened short‐term and long‐term pain and functional deterioration . Addressing delays in therapy adjustment is important for RA patients with MHDAS, which may increase the negative impact of the disease on current and future symptoms and quality of life.…”
Section: Introductionmentioning
confidence: 99%